Massive Hemoperitoneum Following Rupture Of A Functional Ovarian Cyst In A Young Woman Receiving Anticoagulation Therapy: A Case Report In King Abdulaziz Hospital - Cluster Health Jeddah 1 (The Review of Diabetic Studies, 2025)
Background:Rupture of functional ovarian cysts is a frequent and usually benign gynecologic event. In patients receiving anticoagulation therapy, however, cyst rupture may lead to severe intraperitoneal hemorrhage with hemodynamic compromise.Case Presentation:A 24-year-old woman on long-term anticoagulation for previous venous thromboembolism presented with sudden severe lower abdominal pain and syncope. On arrival, she was hypotensive and tachycardic with signs of acute blood loss. Laboratory investigations revealed significant anemia. Bedside ultrasonography demonstrated large-volume intraperitoneal free fluid, and contrast-enhanced computed tomography confirmed massive hemoperitoneum secondary to rupture of a right-sided functional ovarian cyst. Anticoagulation was withheld, resuscitation with blood products was initiated, and the patient underwent emergency laparoscopic surgery. Intraoperatively, active bleeding from a ruptured ovarian cyst was identified and controlled. The patient recovered without complications and was discharged with a revised anticoagulation plan.Conclusion:This case highlights a rare but life-threatening complication of anticoagulation therapy in women of reproductive age. Prompt recognition, early imaging, multidisciplinary management, and timely surgical intervention are essential to prevent morbidity and mortality.